Acute heart failure with improved ejection fraction in a middle-aged patient with myocarditis and COVID-19 infection - Tomaszewska, Małgorzata; Rzesoś, Patrycja; Dudek, Magdalena; Janus, Magdalena; Straburzyńska-Migaj, Ewa (Journal of Medical Science, 2025)
This clinical image describes the management of a 48-year-old male with a history of asthma, anxiety-depressive disorder, and prior COVID-19 infection, who was diagnosed with NYHA Class IV heart failure with reduced ejection fraction due to myocarditis. The patient received an intensive heart failure treatment regimen, including ramipril, eplerenone, bisoprolol, dapagliflozin, ivabradine, and loop diuretics, resulting in a notable clinical improvement and a subsequent reduction in NT-proBNP levels. Upon follow-up, the initiation of sacubitril/valsartan over four months further enhanced functional capacity, leading to an increase in left ventricular ejection fraction to 41% and a decrease in NT-proBNP to 315 pg/ml. Due to these substantial improvements, the need for implantable cardioverter-defibrillator implantation was deemed unnecessary. This case underscores the necessity for early and intensive management of acute heart failure in patients with reduced ejection fraction to facilitate significant recovery. It highlights the rising incidence of myocarditis-related heart failure and emphasises the need for further investigations to optimise therapeutic strategies for patients with restored left ventricular function.